PitNETs and the gut microbiota: potential connections, future directions - Nie, Ding; Li, Chuzhong; Zhang, Yazhuo (Frontiers in Endocrinology, 2023)
The role of the gut microbiome has been widely discussed in numerous works of literature.The biggest concern is the association of the gut microbiome with the central nervous system through the microbiome-brain-gut axis in the past ten years. As more and more research has been done on the relationship between the disease of the central nervous system and gut microbes. This fact is being revealed that gut microbes seem to play an important role from the onset and progression of the disease to clinical symptoms, and new treatments. As a special tumor of the central nervous system, pituitary neuroendocrine tumors ( PitNETs ) are closely related to metabolism, endocrinology, and immunity. These factors are the vectors through which intestinal microbes interact with the central nervous system. However, little is known about the effects of gut microbes on thePitNET. In this review, the relationship of gut microbiota in PitNETs is introduced, the potential effects of the gut-brain axis in this relationship are analyzed, and future research directions are presented.